Ответы и объяснения

2013-02-15T10:10:52+00:00

X^2 +7x = 0                                     49x^2 - 9= 0                               x^2 + 25 = 0
дискриминант = 49 - 0 = 49       дискриминант = 0 +1764     x^2 = -25
х1 = (-7 -7) \ 2 = -7                          x1 = 0-42= -42                         x = + или - 25

х2 = (-7 +7 ) \ 2 = 0                         x2 = 0+42 = 42
  

15 - 2у= 8y^2 + 3x(у+5)                  3(x^2 + 5 ) = 4x^2 + x(1 -x)       -2x^2 +6 = 3(x^2 + x +2)
8у^2 + 3x(y+5)  + 2y =15                 3x^2 + 15 = 4x^2 + x- x^2         -2x^2 +6= 3x^2 +3x +6

8у^2 + 3xy + 15x + 2y = 15              -x^2 +x^2 = x-15                         -5x^2 - 3x = 0

                                                             x-15 = 0                                      дискрим= 9 +0 = 9

                                                             x=15                                            x1=(3 -3) \ -4 = 0

                                                                                                                   x2 = (3+3)\ -4 = -1.5